Actions’ system for continuous improvement in the functioning of disciplinary groups - Mabel Rocha Vázquez; María Isabel Mentecón Ledo (Medisur)
Foundation: The conformation and organization of the Higher Education study plans in Cuba demand the constant search for alternatives that make it possible to perfect the methodological work. Objective: develop a system of actions that contributes to improve the function of disciplinary groups. Methods: development research with a materialist dialectical approach, carried out at the Cienfuegos Medical Sciences University in 2022. Methods were applied at the empirical, theoretical and mathematical statistical levels that together allowed the intended objective to be achieved. The proposal was organized into the diagnosis, design and validation stages. Results: identified potentialities and limitations in the functioning of the disciplinary groups in the institution, aspects considered when proposing planning, organization, execution and control actions for continuous improvement, which particularize aspects for those groups that focus on work practice by constitute education at work as a fundamental principle and organizational form in Cuban Medical Education. The validation of the proposal confirmed its value, so implementing it is the challenge to continue betting on the quality of the processes at the university. Conclusions: the proposed actions are derived from the diagnosis carried out and in an integrated manner contribute to achieving greater effectiveness in the direction of that organizational level for the methodological work in the institution and therefore its operat.